2021
DOI: 10.1016/j.jadohealth.2021.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Adolescent Resilience During the COVID-19 Pandemic: Cognitive Reappraisal and Humor

Abstract: The COVID-19 pandemic and efforts to slow the spread of disease have particularly affected the lives of adolescents. Many studies have recently identified the risks to adolescent mental health posed by the COVID-19 pandemic, yet few have identified the markers of resilience to the events and concerns associated with the pandemic's lived experience. This study examined the moderating role of psychosocial resources in the association between the tangible and emotional experiences of the COVID-19 pandemic and sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 38 publications
(34 reference statements)
5
35
0
4
Order By: Relevance
“…Similar to patterns observed in the context of community-level disasters, growing evidence demonstrates that those exposed to a greater number of pandemic-related stressors are at particularly elevated risk for the onset of mental health problems during the COVID-19 pandemic ( Cohodes, McCauley, & Gee, 2021 ; Kuhlman, Straka, Mousavi, Tran, & Rodgers, 2021 ; Kujawa, Green, Compas, Dickey, & Pegg, 2020 ). Several longitudinal studies have demonstrated associations between the degree of exposure to pandemic-related stressors and increases in symptoms of psychopathology during the pandemic, controlling for pre-pandemic symptom levels, in children, adolescents, and adults in a variety of cultural contexts ( Hawes, Szenczy, Klein, Hajcak, & Nelson, 2021 ; Pereira et al, 2021 ; Rosen et al, 2021 ; Weissman et al, 2021 ).…”
Section: Cumulative Riskmentioning
confidence: 70%
See 1 more Smart Citation
“…Similar to patterns observed in the context of community-level disasters, growing evidence demonstrates that those exposed to a greater number of pandemic-related stressors are at particularly elevated risk for the onset of mental health problems during the COVID-19 pandemic ( Cohodes, McCauley, & Gee, 2021 ; Kuhlman, Straka, Mousavi, Tran, & Rodgers, 2021 ; Kujawa, Green, Compas, Dickey, & Pegg, 2020 ). Several longitudinal studies have demonstrated associations between the degree of exposure to pandemic-related stressors and increases in symptoms of psychopathology during the pandemic, controlling for pre-pandemic symptom levels, in children, adolescents, and adults in a variety of cultural contexts ( Hawes, Szenczy, Klein, Hajcak, & Nelson, 2021 ; Pereira et al, 2021 ; Rosen et al, 2021 ; Weissman et al, 2021 ).…”
Section: Cumulative Riskmentioning
confidence: 70%
“…Emerging evidence also suggests that the link between pandemic-related stress and psychopathology is weaker in adolescents and adults who engage in high levels of cognitive reappraisal. Specifically, use of cognitive reappraisal moderated the association between perceived stress and symptoms of anxiety among adults during the early phase of the pandemic ( Xu et al, 2020 ) and between exposure to pandemic-related stressors and symptoms of depression and anxiety in adolescents ( Kuhlman et al, 2021 ). One study of healthcare workers additionally reported a positive influence of cognitive reappraisal on levels of emotional exhaustion ( Wang et al, 2021 ).…”
Section: Stress Appraisal and Reappraisalmentioning
confidence: 99%
“…Naturalistic observations, for example, have found that caregivers’ expressions of their own positive emotion, physical touch, and engagement sustained school-aged children’s expression of positive emotion (Bai et al, 2016 ). There is also an emerging focus on the link between humor and emotion regulation in both adults (Braniecka et al, 2019 ; Horn et al, 2019 ; Wu et al, 2021 ) and children and adolescents (Kuhlman et al, 2021 ; Mireault et al, 2015 ). A recent study found that infants aged five to seven months smiled more frequently, longer, and more quickly in response to an absurd event when caregivers provided cues that the event was humorous than when they provided neutral cues, suggesting caregivers can begin shaping their children’s understanding of humor very early on (Mireault et al, 2015 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…In another study, caregivers’ use of humor was associated with greater competence in emotion regulation among five- and six-year-old children, with parenting warmth mediating the relationship between maternal humor and children’s emotion regulation (Oh & Hwang, 2018 ). In a study of adolescents, self-reported use of humor appeared to have a protective effect against the impact of the COVID-19 pandemic on psychiatric symptoms (Kulman et al, 2021 ). In line with a strengths-based perspective, promoting caregivers’ use of coregulation strategies that also attend to positive emotions, including those that arise from humorous experiences, may not only benefit children’s individual development, but may also enhance the quality of interactions within various family subsystems.…”
Section: Future Directionsmentioning
confidence: 99%
“…A more hopeful note for some was struck towards the end, when it was suggested that young people with night owl chronotypes might benefit, and that all might benefit from reduced travelling times. Kuhlman et al, (2021) explored the impact of the pandemic on sleep disturbance as part of a wider study into predictors of adolescent resilience during COVID-19. The study found that teenagers who had high levels of both affiliative and self-effacing humour (using the Humour Styles questionnaire) had a moderated impact of the pandemic on their sleep.…”
Section: The Impact On Mental Healthmentioning
confidence: 99%